2021
DOI: 10.3390/brainsci11060674
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Conversion from MCI to AD Combining Multi-Modality Data and Based on Molecular Subtype

Abstract: Alzheimer’s disease (AD) is a neurodegenerative brain disease in the elderly. Identifying patients with mild cognitive impairment (MCI) who are more likely to progress to AD is a key step in AD prevention. Recent studies have shown that AD is a heterogeneous disease. In this study, we propose a subtyping-based prediction strategy to predict the conversion from MCI to AD in three years according to MCI patient subtypes. Structural magnetic resonance imaging (sMRI) data and multi-omics data, including genotype d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…We also used the MSSM features to predict MCI patients who progress to AD dementia within 3 years and it showed prominent prognostic performance (AUROC = 0.908, AURPC = 0.910), which is comparable to but slightly higher than the cortical thickness-based model that used similar procedures and models based on hippocampal volume or RAVLT cognitive test scores. It also outperformed models that use one or more MRI features of cortical thickness, hippocampal volume, and volumetric features, ( Sørensen et al, 2016 , Popuri et al, 2020 , Zhu et al, 2017 ), MRI-based CNN models, ( Gao et al, 2020 , Lu et al, 2018 ), a model that combines MRI, genotypes, and gene expression profiles ( Li et al, 2021 ), a model combining MRI morphometrics, CSF and cognitive measures ( Ye et al, 2012 ), and models using PET or PET combined with MRI, ( Liu et al, 2014 , Lu et al, 2018 , Zhu et al, 2017 ). Higher performance was reported in a few studies that used longitudinal MRI, ( Sun et al, 2017 ) and that combined MRI with cognitive performance ( Tong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used the MSSM features to predict MCI patients who progress to AD dementia within 3 years and it showed prominent prognostic performance (AUROC = 0.908, AURPC = 0.910), which is comparable to but slightly higher than the cortical thickness-based model that used similar procedures and models based on hippocampal volume or RAVLT cognitive test scores. It also outperformed models that use one or more MRI features of cortical thickness, hippocampal volume, and volumetric features, ( Sørensen et al, 2016 , Popuri et al, 2020 , Zhu et al, 2017 ), MRI-based CNN models, ( Gao et al, 2020 , Lu et al, 2018 ), a model that combines MRI, genotypes, and gene expression profiles ( Li et al, 2021 ), a model combining MRI morphometrics, CSF and cognitive measures ( Ye et al, 2012 ), and models using PET or PET combined with MRI, ( Liu et al, 2014 , Lu et al, 2018 , Zhu et al, 2017 ). Higher performance was reported in a few studies that used longitudinal MRI, ( Sun et al, 2017 ) and that combined MRI with cognitive performance ( Tong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegeneration measures from imaging are associated with disease severity and prognosis ( Benvenutto et al, 2018 , Brickman et al, 2018 , Aziz et al, 2017 ), and MRI is an alternative tool to assess AD neurodegeneration, which is safe, non-invasive, and more accessible in clinical settings. Advances in brain imaging with machine learning techniques made it possible to identify individuals with AD dementia or mild cognitive impairment (MCI) ( Belathur Suresh et al, 2018 , Cho et al, 2012 , Suk et al, 2014 , Sarraf et al, 2019 , Bloch and Friedrich, 2021 , Lin et al, 2018 , Li et al, 2021 , Guo et al, 2017 , Ye et al, 2012 , Gao et al, 2020 , Shi et al, 2018 , Liu et al, 2014 , Wolz et al, 2011 , Lu et al, 2018 , Sørensen et al, 2016 , Popuri et al, 2020 , Sun et al, 2017 , Tong et al, 2017 , Allison et al, 2019 , Noor et al, 2019 , Choi et al, 2020 , Zhang et al, 2011 , Westman et al, 2012 , Park et al, 2017 , Davatzikos et al, 2008 , Desikan et al, 2009 , Sørensen et al, 2017 , Zhu et al, 2017 , McEvoy et al, 2009 , Magnin et al, 2009 , Mattsson et al, 2019 , Janghel and Rathore, 2021 ) using fairly routine structural MRI procedures and therefore MRI provides an optimal ‘first pass’ screen of patients. A simple metric such as hippocampal volume is sensitive to AD neurodegeneration; however hippocampal volume is impacted by a range of conditions and is not specific to AD.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that MAPKs are the principal modulators of the cognitive impairment and decline independently of the APOE genotype. According to Li et al (2021) , conversion risk differs between patient groups presenting distinct genomic, proteomic and neuroimaging features. Using proteomics, genomics and transcriptomics data derived from brain tissue, Seyfried et al identified a genetic risk locus for AD encoding genes involved in microglia and oligodendrocyte function associated with cognitive decline ( Seyfried et al, 2017 ).…”
Section: Molecular Alterations With Clinical Relevancementioning
confidence: 99%
“…Mild cognitive impairment (MCI) is a neurological disorder occurring mainly in older people with cognitive deficits that are not severe enough to warrant a diagnosis of dementia [ 1 ]. It has been classified as a prodromal stage of a variety of dementing disorders, including Alzheimer’s disease (AD) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%